Sense (International Journal of Scientific Research and Management (IJSRM), 2023)
In science, it is a very common question that what is the sense of our result. If one understands the sense of result, then they could be used somewhere else to do something else. In [1], I mention that results in machine learning have to be justified mathematically or in other words measured by correctness. In [2], I describe intelligence by correctness. In this paper, I describe what is sense that will lead to understanding of answers and results in science.